(untitled) (Bangladesh Journal of Infectious Diseases, 2026)
Background: In Bangladesh, molecular testing for HBV DNA is largely restricted to tertiary healthcare facilities due to the high cost, technical complexity, and challenges of plasma sample collection, storage, and transport. Dried blood spot (DBS) sampling, obtained through finger-prick collection, offers a minimally invasive, low-cost, and field-friendly alternative for HBV DNA detection in resource-limited settings. Objective: This present study was undertaken to detect HBV DNA in DBS and plasma by real-time PCR. Methodology: The study was conducted in the Department of Virology at Dhaka Medical College (DMC), Dhaka, Bangladesh, from January 2024 to December 2024 for a period of one year. This cross-sectional study included 80 confirmed HBV-infected patients recruited from the Departments of Hepatology, Medicine, and Gastroenterology at Dhaka Medical College Hospital (DMCH), Bangladesh. Paired plasma and DBS samples were analyzed for HBV DNA using real-time polymerase chain reaction (PCR). Sensitivity, specificity, accuracy, and correlation between plasma and DBS results were calculated. Results: DBS demonstrated a sensitivity of 96.1%, specificity of 100%, and accuracy of 96.4% for HBV DNA detection compared with plasma. The mean HBV DNA load was 3.50 log₁₀ IU/mL in plasma and 2.86 log₁₀ IU/mL in DBS, showing a strong positive correlation (R = 0.8062). Conclusion: DBS is a valid and practical alternative sample to plasma. Bangladesh Journal of Infectious Diseases, December 2025;12(2):300-305